2021
DOI: 10.1016/j.ajpath.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin–Ephrin-B1–Na+/H+ Exchanger Regulatory Factor 2–Ezrin–Actin Axis Is Critical in Podocyte Injury

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…However, some changes in these proteins were evident in SLK KO GECs and mice, particularly in the context of adriamycin. A recent study has proposed ezrin linking F‐actin with ephrin B1, and ephrin B1 interacting with nephrin (Fukusumi et al., 2021 ). This pathway involving ezrin could potentially be regulated by SLK.…”
Section: Discussionmentioning
confidence: 99%
“…However, some changes in these proteins were evident in SLK KO GECs and mice, particularly in the context of adriamycin. A recent study has proposed ezrin linking F‐actin with ephrin B1, and ephrin B1 interacting with nephrin (Fukusumi et al., 2021 ). This pathway involving ezrin could potentially be regulated by SLK.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that phosphorylation of ezrin was increased in glomeruli of rCrb2-immunized mice in vivo and in Crb2-expressing immortalized mouse podocytes exposed to anti-Crb2 antibody in vitro . Because the intracellular domain of Crb2 is known to interact with ezrin, a known linker of the membrane protein and the actin cytoskeleton, 29 , 30 it is plausible that Crb2 antibodies activate phosphorylation of ezrin by crosslinking and aggregating Crb2. Indeed, Crb family proteins are believed to form homophilic binding 49 and our results support the capacity of Crb2 to oligomerize (Supplemental Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…22 The phosphorylated ERM proteins act as a critical linker between the plasma membrane and the actin cytoskeleton. 29,30 Thus, Crb2 could work as a signaling molecule and regulate the actin cytoskeleton in podocytes via ERM proteins and/or nephrin. Conversely, altered Crb2 signaling pathways may result in actin derangement and FP effacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In glomerular podocytes, Ezrin has also been reported to form a multi-protein complex with NHERF2 and podocalyxin [ 179 ], and the loss of Ezrin reduced susceptibility to glomerular injury in mice [ 180 ]. A recent study found that this protein complex also interacts with nephrin and ephrin-B1, forming an axis critical to podocyte injury [ 181 ].…”
Section: Ezrin Interacts With Metastasis-related Proteinsmentioning
confidence: 99%